Drosophila homologues of the transcriptional coactivation complex subunits TRAP240 and TRAP230 are required for identical processes in eye-antennal disc development. - Treisman, J.E. (Development, 2001)
We have identified mutations in two genes, blind spot and kohtalo, that encode Drosophila homologues of human TRAP240 and TRAP230, components of a large transcriptional coactivation complex homologous to the yeast Mediator complex. Loss of either blind spot or kohtalo has identical effects on the development of the eye-antennal disc. Eye disc cells mutant for either gene can express decapentaplegic and atonal in response to Hedgehog signaling, but they maintain inappropriate expression of these genes and fail to differentiate further. Mutant cells in the antennal disc lose expression of Distal-less and misexpress eyeless, suggesting a partial transformation towards the eye fate. blind spot and kohtalo are not required for cell proliferation or survival, and their absence cannot be rescued by activation of the Hedgehog or Notch signaling pathways. These novel and specific phenotypes suggest that TRAP240 and TRAP230 act in concert to mediate an unknown developmental signal or a combination of signals.